William James' Concept of Religion: An Empirical Theory and Its Implementation in the Religious Context of Indonesia - Remegises Danial Yohanis Pandie (Institut Agama Kristen Negeri Toraja, 2023)
Abstract: The purpose of writing this article is to analyze the concept of religion from the perspective of William James. This paper refers to James's framework of thinking about the way of religion and its urgency for religions that are adhered to by humans. As explained by James that being a religious person means belief in an invisible order that really exists, so that it produces a real effect in the world. The method used in this research is literature study which refers to references related to the topic raised. In this study, researchers found that the concept of William James can be implemented in Indonesia because it opens the framework of the Indonesian people's thinking about the way of religion through experience, knowledge, moral awareness and acceptance that leads to peace.Â Keywords: priest, single, church, ministry, vocation The Concept of Religion, Empirical Theory, William James.